Indian painting : essays in honour of Karl J. Khandalavala - Khandalavala, Karl J.; Goswamy, B. N., 1933-; Bhatia, Usha.; Lalit Kala Akademi (New Delhi : Lalit Kala Akademi, 1995)
Festschrift in honor of Karl J. Khandalavala; comprises essays on Indian painting and sculpture.
Includes bibliographical references.
"Select bibliography of the writings of Karl J. Khandalavala": p. 475-480.
Keywords: Painting, Indic -- India; Architecture and society -- India; India -- Social life and customs